The parameter estimation of the multivariate matrix regression models - Lin, Zerong; He, Lingling; Wu, Tian; Xu, Changqing (Statistics, Optimization & Information Computing, 2018)
In this paper, we consider the parameter matrix estimation problem of the multivariate matrix regression models. We approximate the parameter matrix B and the covariance matrix by using the method of the maximum likelihood estimation, together with the Kronecker product of matrices, vectorization of matrices and matrix derivatives.